Hot carrier degradation of extended drain N-channel metal-oxide-semiconductor - Kok, Ignatius Jin Yan (Nanyang Technological University, 2021)
The objective of the project targets the understanding of how the Extended Drain Metal Oxide Semiconductor (EDMOS) operates under a variety of stressing conditions. The EDMOS is seen as a potential successor to Metal-Oxide-Semiconductor Field Effect Transistors (MOSFETS) used in power amplifiers, particularly those used in telecommunication systems. EDMOS of different sizes were used to understand the impact of Hot Carrier Stress on the device due to a myriad of factors. Different methodologies used in Integrated Circuit (IC) reliability testing, not limited to the comparison of MOSFET transfer characteristics and Parasitic Capacitance measurement, have been used to study the long-terms effects of stress on the EDMOS under accelerated conditions.